2010
DOI: 10.1007/s10029-010-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Omental incarceration may cause hydrocele and this hydrocele confused simple or scrotal hydrocele

Abstract: In the light of our experience, a scrotal approach to hydrocele repair in children would be difficult in cases of incarceration with hernia. Omental incarceration may cause hydrocele, and this hydrocele can be confused with normal hydrocele. Therefore, we would continue to recommend an inguinal approach for childhood hydroceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…Omental incarceration causing hydrocele has been reported [15]. Here, the average age was 4.5 years, a little bit lower than our series.…”
Section: Discussioncontrasting
confidence: 69%
“…Omental incarceration causing hydrocele has been reported [15]. Here, the average age was 4.5 years, a little bit lower than our series.…”
Section: Discussioncontrasting
confidence: 69%
“…As the sensitivity of the US against testicular torsion is as high as 88.9–100% [ 1 , 2 ] and the US in this case showed clear blood flow into both testes, we had to rule out another disease that required emergent surgery—incarcerated intestine or omentum into the inguinal canal. Even the highest sensitivity of the US for incarcerated inguinal hernia is 91% [ 3 ], and thus, the possibility of an incarcerated hernia could not be eliminated. Therefore, we proceeded to emergent surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, however, there was no ischemia of the omentum; nor was the hydrocele communicating with abdominal cavity, suggesting other reasons exist for hydrocele inflammation. Clinically, it was reported that omentum often form adhesions to inflamed regions such as the patient's PV [ 3 ]. In our case, possibly, omentum caused inflammatory changes in the PV and the inflammation spread to the hydrocele wall, although this is just a speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Omental infarction is a rare painful condition that mimics appendicitis [ 4 ], and cholecystitis [ 5 ]. Omental incarceration in an inguinal hernia is most often of a simple evolution [ 6 ], but can be complicated with omental infarct causing acute scrotum. This is exceedingly rare complication in children to best of our knowledge, the only one case of omental infarct in a hernial in children has been reported by Patel et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%